An explanatory, quantitative study to understand the behaviour of low-income household’s online shopping behaviour - Midgley, Michael (The IIE, 2016)
The research study looks at understanding the behaviour of low-income household’s online shopping behaviour and the impact of online retail in South Africa. This research shall deliver value to both businesses looking to compete within the lower income segment of the market and consumers in understanding the benefits of online shopping. There are exactly 75 percent of people who are what is considered below middle class within this country and thus there is clear value to be obtained (Visagie, 2013). The study will address the reasons why low income households act the way they do when it comes to online shopping. The study further looks at the value that can be captured when targeting the lower income segment of the market. This study is worth investigating as e-commerce is on the rise in many countries yet in South Africa it has not reached its full potential. The purpose of the study will educate consumers and retailers on the underlying problems with online shopping, the unrealised benefits that it contains and give a comparison between the low income consumer groups’ and the higher income consumer groups’ buying behaviour. The research proposal used a quantitative approach in order to conduct research. This approach enabled the study to utilise numerical and quantitative data in order to predict and tabulate the data obtained from the sample groups. The research study made use of cross sectional surveys to obtain data from respondents of the study. The low income household’s sample was further communicated to through an intermediary being a field worker. The survey was handed out to two sample groups, namely low income earning individuals (social class) and students between the ages of 18 and 26. Online shopping is a very innovative technique and one which the researcher sees as the future of purchasing goods within South Africa. However for it to work in South Africa there needs to be structural changes within the country and security risks need to be fixed.
Keywords: Consumer behaviour; E-commerce; Online shopping